Genome-wide identification and characterization of JAZ gene family in upland cotton (Gossypium hirsutum) - Li, Wen; Xia, Xiao-Cong; Han, Li-Hong; Ni, Ping; Yan, Jing-Qiu; Tao, Miao; Huang, Geng-Qing; Li, Xue-Bao (Scientific reports, 2017)
Plant JAZ (Jasmonate ZIM-domain) proteins play versatile roles in multiple aspects of plant development and defense. However, little is known about the JAZ family in allotetraploid upland cotton ( Gossypium hirsutum ) so far. In this study, 30 non-redundant JAZ genes were identified in upland cotton through genome-wide screening. Phylogenetic analysis revealed that the 30 proteins in cotton JAZ family are further divided into five groups (I – V), and members in the same group share highly conserved motif structures. Subcellular localization assay demonstrated that GhJAZ proteins are localized in the cell nucleus. Quantitative RT-PCR analysis indicated that GhJAZs display different expression patterns in cotton tissues, and most of them could be induced by Jasmonic (JA). Furthermore, some GhJAZ genes are preferentially expressed in cotton ovules and fibers, and showed differential expression in ovules of wild type cotton and fiberless mutant ( fl ) during fiber initiation. GhJAZ proteins could interact with each other to form homodimer or heterodimer, and they also interacted with some JA signaling regulators and the proteins involved in cotton fiber initiation. Collectively, our data suggested that some GhJAZ proteins may play important roles in cotton fiber initiation and development by regulating JA signaling as well as some fiber-related proteins.